Proceedings of the 12th European Conference on Combinatorics, Graph Theory and Applications 2023
DOI: 10.5817/cz.muni.eurocomb23-007
|View full text |Cite
|
Sign up to set email alerts
|

A lower bound for set-colouring Ramsey numbers

Abstract: The set-colouring Ramsey number $R_{r,s}(k)$ is defined to be the minimum $n$ such that if each edge of the complete graph $K_n$ is assigned a set of $s$ colours from $\{1,\ldots,r\}$, then one of the colours contains a monochromatic clique of size $k$. The case $s = 1$ is the usual $r$-colour Ramsey number, and the case $s = r - 1$ was studied by Erd\H{o}s, Hajnal and Rado in 1965, and by Erd\H{o}s and Szemerédi in 1972. The first significant results for general $s$ were obtained only recently, by Conlon, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…After the first version of this paper appeared on arXiv, Aragão, Collares, Marciano, Martins and Morris [3] showed that the bound in Lemma 4.2 is tight up to a logarithmic factor when sprefix≈rprefix−r$$ s\approx r-\sqrt{r} $$, thereby ruling out any hope of substantially improving () by the route suggested above.…”
Section: Discussionmentioning
confidence: 99%
“…After the first version of this paper appeared on arXiv, Aragão, Collares, Marciano, Martins and Morris [3] showed that the bound in Lemma 4.2 is tight up to a logarithmic factor when sprefix≈rprefix−r$$ s\approx r-\sqrt{r} $$, thereby ruling out any hope of substantially improving () by the route suggested above.…”
Section: Discussionmentioning
confidence: 99%